2006
DOI: 10.1593/neo.06430
|View full text |Cite
|
Sign up to set email alerts
|

Global Expression-Based Classification of Lymph Node Metastasis and Extracapsular Spread of Oral Tongue Squamous Cell Carcinoma

Abstract: Regional lymph node metastasis is a critical event in oral tongue squamous cell carcinoma (OTSCC) progression. The identification of biomarkers associated with the metastatic process would provide critical prognostic information to facilitate clinical decision making for improved management of OTSCC patients. Global expressional profiles were obtained for 25 primary OTSCCs, where 11 cases showed lymph node metastasis (pN+) histologically and 14 cases were nonmetastatic (pN-). Seven of pN+ cases also exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 38 publications
4
94
2
Order By: Relevance
“…This supports our hypothesis that molecular determinants of ECS are present in the primary tumour. In a recent meta-analysis of over 60 studies of differential gene-expression profiling in HNSCC, one study of a limited number of cases predicted ECS by geneexpression analysis from primary site tissue (Zhou et al, 2006;Yu et al, 2008). It is also evident from many studies that there is a high risk for false discovery, and careful validation is mandated before establishing clinical biomarkers (Mroz and Rocco, 2012;van Hooff et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…This supports our hypothesis that molecular determinants of ECS are present in the primary tumour. In a recent meta-analysis of over 60 studies of differential gene-expression profiling in HNSCC, one study of a limited number of cases predicted ECS by geneexpression analysis from primary site tissue (Zhou et al, 2006;Yu et al, 2008). It is also evident from many studies that there is a high risk for false discovery, and careful validation is mandated before establishing clinical biomarkers (Mroz and Rocco, 2012;van Hooff et al, 2012a).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the expressional changes of MTUS1 genes at mRNA level, the quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was performed as described previously [15] on 10 HNSCC cell lines and normal oral keratinocyte (NHOK), as well as 10 paired normal and oral tongue cancer tissues samples (see Supplement Table 2 for the descriptions of the oral tongue cancer tissues). The RNA from cell lines was isolated using Qiagen RNeasy kit.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial tumor suppressor gene 1 (MTUS1) is one of the candidate genes that reside in this genomic region, which was initially identified as a potential tumor suppressor gene in pancreatic cancer [14]. Our recent study suggested that the reduction of MTUS1 expression may be associated with advanced oral tongue SCC [15]. The reduced expression of MTUS1 has also been observed in colon cancer, ovarian cancer and pancreatic cancer [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently validated the microarray results by qRT-PCR of several genes, ADCY7, ARGHDIB, BAMBI, FOXG1, FSCN1, FUCA1, GFPT2, ITPR3, ITGA4, LSP1, NCAM1, NUDT14, RGS20, RHOF, and RIAM, that have already been implicated in cell migration, adhesion, or angiogenesis (28,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). The results from qRT-PCR analysis (Fig.…”
Section: Differential Gene Expression Analysis Of Pr9692shmock and Prmentioning
confidence: 99%